Buoyancy-affected backward-facing step flow with heat transfer at low Prandtl number. (October 2016) - Niemann, Martin; Fröhlich, Jochen
Highlights: First DNS of turbulent backward-facing step flow at low Prandtl number. Computation of large number of statistical quantities. Substantial influence of buoyancy on mean flow and heat transfer detected. Data constitute reference for turbulence modeling at low Prandtl number. Abstract: Motivated by applications in concentrating solar power plants, the paper presents direct numerical simulations of the turbulent upward-directed flow of a liquid metal in a vertical channel. One of the walls features a backward-facing step with the vertical wall behind the step being heated. The paper addresses the impact of buoyancy effects by comparing two simulations, one with the buoyancy term removed from the equations, the other one with a Richardson number of 0.338. After a thorough validation detailed statistical data for both cases are provided. Due to the buoyancy forces acting on the fluid at the heated wall, the flow field is substantially altered and recirculation is considerably diminished. The altered flow field and the increased advection of temperature increase heat transfer at the heated wall. The differences in the turbulent heat fluxes are thoroughly discussed and related to the altered flow conditions. The results contribute to the physical understanding of buoyancy effects on turbulent heat transfer in the considered regime. Furthermore, the generated data allows the validation and improvement of turbulence models for turbulent heat transfer in the range of low Prandtl numbers.